Interview with Prof. Julian Müller: Reflections on a career in Practical Theology - J. Meyer (Acta Theologica)
Emeritus Prof. Julian Müller is a distinguished practical and pastoral theological scholar celebrated for his contributions to interdisciplinary and postfoundational studies, a narrative approach towards pastoral theological practices, and research on pastoral care and Ubuntu. This interview delves into Prof. Müller’s journey from ministry to academia, the evolution of his research interests, and his insights on the future of practical and pastoral theology in South Africa. Prof. Müller’s reflections offer valuable perspectives on the dynamic nature of practical theology and its relevance in addressing contemporary challenges.